A novel approach to brain connectivity reveals early structural changes in Alzheimer's disease. (23rd July 2018) - La Rocca, Marianna; Amoroso, Nicola; Monaco, Alfonso; Bellotti, Roberto; Tangaro, Sabina
Abstract: Objective : Recent studies have shown that complex networks along with diffusion weighted imaging (DWI) can be efficient and promising techniques for early detection of structural pathological changes in Alzheimer's disease. Besides, connectivity studies, specifically assessing the organization of a graph and its topology, could represent the best chance to discover how brain activity is shaped and driven. Accordingly, we propose a methodology to evaluate how Alzheimer's disease affects brain networks through a novel way to look at graph connectivity. In fact, we use the combination of network features related to brain organization with network features related to the variations in connectivity between several subjects. Approach : From a DWI brain scan we reconstruct a probabilistic tractography by evaluating the number of white matter fibers connecting two anatomical districts, thus obtaining a weighted undirected network. The nodes of this network are the cerebral regions provided by the reference brain atlas, the weights are the intensity of linkage among them. We investigated brain connectivity graphs retrieved from a set of 222 publicly available DWI scans from the Alzheimer's Disease Neuroimaging Initiative (ADNI): 47 Alzheimer's disease (AD) patients, 52 normal controls (NC) and 123 mild cognitive impairment (MCI) subjects, this latter cohort includes 85 early and 38 late MCI subjects, EMCI and LMCI respectively. Main results : The proposed brain connectivity approach effectively characterizes Alzheimer's disease, especially in its early stages. In fact, MCI is a prodromal phase of Alzheimer's disease. We report a accuracy for the discrimination of NC and AD subjects and accuracies of and for the discrimination of MCI from respectively NC and AD subjects. Significance : Our complex network approach offers an innovative and effective instrument to model brain connectivity and detect in DWI tractographies early changes due to Alzheimer's.